Intensitas dan Prevalensi Endoparasit pada Ikan Layang (Decapterus russeli) yang didaratkan di Pantai Kedonganan Bali - Amayliana Ajeng Nastiti; Pande Gde Sasmita Julyantoro; Dewa Ayu Angga Pebriani; Endang Wulandari Suryaningtyas (Current Trends in Aquatic Science, 2021)
The Indian scad (Decapterus russeli) is a pelagic fish that has high economic value, found throughout the Indonesian waters. The availability of Indian scad resources makes this fish easy to find, especially in Kedonganan Beach, Bali. The use of Indian scad for human consumption makes it necessary to pay attention to the quality of indian scad in order to avoid fish diseases, such as parasites. The attack of endoparasites in Indian scad can be zoonotic, which can be dangerous for humans who consume them, so research is needed to determine the density of endoparasite attacks and the percentage of endoparasites in indian scad. Samples of Indian scad (D. russeli) were obtained randomly from PPI Kedonganan and Kedonganan Fish Market. The observed organs were intestines, gonads and liver. The research was conducted for 1 month from 16 December 2020 to 17 January 2021 and fish samples were taken by random sampling. There were 35 fish samples (D. russeli) examined. The endoparasites found were Anisakis sp. (316 individuals), Camallanus sp. (15 individuals), and Lecithocirium sp. (33 individuals). The highest intensity in the genus Anisakis was 9.2 ind/fish and was classified as moderate infection and the highest prevalence was also in the Anisakis genus, which was 97.14% with (almost always categories), 60% of the genus Lecithocirium (very frequent categories), and the Camallanus genus of 28.50% with (frequent category).